Implementation of the Internal Audit Capability Model (IA-CM) in Increasing The Capability of APIP at Inspectorat Office of Binjai City - Rachmani Tarigan; Deliana Deliana; Meily Surianti (Universitas Islam Bandung, 2023)
This research is aimed to analyse the Capability level of the Government Internal Oversight Apparatus (APIP) at the Inspectorate Office of Binjai City which refers to the Internal Audit Capability Model (IA-CM) standard that is generally accepted throughout the world by using internal audit elements to analyse elements that affect APIP's lagging behind that unable to reach the target and provide strategic input carried out by the Binjai City Inspectorate to increase APIP capabilities which have not been maximized. This research is qualitative research using descriptive analysis. In terms of analyzing research data, the authors used data collection techniques by observing, documenting and interviewing. While the data analysis technique used is a descriptive analysis method. The informants in this research were government internal control apparatus (APIP) at the Inspectorate of the city of Binjai. Based on the research results, based on the APIP Capability assessment using the Internal Audit Capability Model (IA-CM) standard, showed that the Binjai City Inspectorate is at level 3 fully integrated where 6 internal audit elements according to the IA-CM Standard have reached level 3. By achieving level 3, there are several things that are still of concern to be improved by APIP Binjai city, namely the quantity and quality of human resources, facilities and infrastructure that are still inadequate and the budget that has not been maximized.